SARS-CoV-2: from origin to treatment and control management strategies - Hezam, Kamal; Almansoub, Hasan; Al-Gheethi, Adel; Saleh, Fuad; Almansob, Yusra; Al-Mekhlafi, Hanadi; Al-Yousofi, Asma; Almezgagi, Maged; Al-Shaebi, Fadhl; Murshed, Dina (Penerbit UTHM, 2020)
The emergence of novel coronavirus (SARS-CoV-2) is marked as the highest pathogenic coronavirus that has crossed from the hosts to the human population in the twenty-first century. The spreading of COVID-19 in different Chinese cities and around the world is travel-related viral spread with the unprecedented nosocomial outbreaks. It has also shown with high case-fatality rates, indeed to urgent prophylactic and therapeutic settings. Scientific advancements of the SARS-CoV-2 pandemic allowed for rapid progress to understand the epidemiology and pathogenesis of SARS-CoV-2. This review highlights the genomic structure of SARS-CoV-2 with the proposed roles of genotype and phenotype of SARS-CoV-2 in pathogenesis and discusses recent results supporting treatment strategies of COVID-19 with a particular focus on how these new insights may facilitate rational development of SARS-CoV-2 for targeted therapies in the future.